On Novel Language Phonology: What Do Factors tell us in Non-native Settings? - Fouda, Essomba; Atechi, Samuel (Archives of Business Research, 2016)
This paper looks into factors affecting the spoken production of Bilingual Two students of the University of Yaounde I. Emphasis is laid on the effect of three main factors (previously spoken language(s), formal instruction and motivation) which are assumed to impact bilinguals’ ultimate attainment in the production of English consonants and vowels. The role of age is discussed incidentally in this paper. The paper follows an inferential reasoning in an attempt to explicate features of CamE and CamFE. It therefore attempts an explanation of the origin of these features, on the one hand, and determine how close to or distant the speech of each set of bilinguals is from the other hand and RP on the other hand, owing to the supposed effect of affecting factors. The paper shows that RP, Cameroon Francophone English (CamFE) and the speech of Anglophone bilinguals share a sizeable number of segmental traits. However, CamFE and English-French bilinguals’ speech differ significantly from RP, and thus have each traits that are peculiar to them alone.  It was inferred that previously spoken language(s)-namely French and Pidgin English- and to a very minor extent age could better account for that. It is also shown that a number of RP renditions are attested in the speech of some bilinguals. Two factors were said to stand at the inception of this: formal instruction and notably motivation.